Mountain roads development in Nepal: engineering geological concerns - Deoja, Birendra B. (Journal of Nepal Geological Society, 2000)
Road construction in the mountainous regions of Nepal has not only added to the road building experience in the rugged mountain terrain but also created awareness that development of linear infrastructure in the mountainous regions requires multidisciplinary approach from social, economic, engineering, environmental, and biotechnical considerations besides substantial engineering-geological inputs. This paper tries to provide a brief account of the practices and developments in mountain-specific planning and management of infrastructure on the basis of experiences from Nepal.